A Computational Design Analysis of UAV's Rotor Blade in Low-Temperature Conditions for the Defence Applications. (6th January 2021) - Chevula, Sreenadh; Chillamcharal, Sankeerth; Maddula, Satya Prasad
Abstract : This paper discusses about the critical situations faced by the Defence operations with drones in the area of Siachen Glacier in the Himalayas. The reasons for the structural failures in drone's rotor blades and the low-performance efficiency of the drones at low-temperature conditions are highlighted. A possible solution to the above-mentioned problems has been addressed by introducing a new boundary design in the rotor blades and composite materials. The results which are shown in this paper are obtained by the computational analysis facility located at the Department of Aerospace Engineering, School of Technology, GITAM (Deemed to be University), Hyderabad. By mimicking the Siachen Glacier atmosphere conditions, the proposed rotor blade design has been analysed in CFD.